Ускорение социально-экономического развития и перспективное планирование - Кириченко В. Н. Вадим Никитович; Куранов Г. О. Геннадий Оразович; Сеченова В. В. Вера Васильевна; Черников Д. А. Дмитрий Александрович; Кириченко Вадим Никитович (Москва, Экономика, 1987)
Авт. указаны на обороте тит. л.